Regeneration of Ficus glomerata Roxb., using shoot tips and nodal explants (Bangladesh Journal of Botany, 2010)
Shoot tips and nodal explants from in vitro growing seedlings of Ficus glomerata Roxb. (Moraceae). showed best shoot induction (88%) on MS medium supplemented with 0.5 mg/l BAP, where maximum number of shoots were produced per culture. In vitro raised shoots rooted well on half strength of MS medium with 2.0 mg/l IBA + 0.1 mg/l NAA. The survival rate of regenerated plantlets was 82%. Key words: Ficus glomerata Roxb.; Shoot proliferation; Micropropagation; Acclimatization DOI: 10.3329/bjb.v39i1.5525Bangladesh J. Bot. 39(1): 47-50, 2010 (June)